Aerobic fitness level typical of elite athletes is not associated with even faster VO2 kinetics during cycling exercise - Figueira, T. R.; Caputo, F.; Machado, C. E. P.; Denadai, B. S. (Journal of Sports Science & Medicine, 2008)
The aim of this study was to address the question if the VO2 kinetics is further improved as the aerobic training status increases from trained to elite level athletes. Maximal oxygen uptake (VO2max), work-rate associated to VO2max (IVO2max) and VO2 kinetics of moderate (Mod) and maximal exercise (Max) were determined in fifty- five subjects. Then, they were assigned into three groups: low (LF), intermediate (IF) and high (HF) aerobic fitness level. In average, the VO2max of LF, IF and HF groups were, respectively, 36.0 ± 3.1, 51.1 ± 4.5 and 68.1 ± 3.9 ml·kg·min-1 (p < 0.05 among each other). VO2 kinetics mean response time of both exercise intensities were significantly faster (p < 0.05) in HF (Mod, 27.5 ± 5.5 s; Max, 32.6 ± 8.3 s) and IF (Mod, 25.0 ± 3.1 s; Max, 42.6 ± 10.4 s) when compared to LF (Mod, 35.7 ± 7.9 s; Max: 57.8 ± 17.8 s). We can conclude that VO2 kinetics is improved as the fitness level is increased from low to intermediate but not further improved as the aerobic fitness level increases from intermediate to high.